Novel Schiff base ligand and its metal complexes with some transition elements. Synthesis, spectroscopic, thermal analysis, antimicrobial and in vitro anticancer activity. (5th January 2016) - Mahmoud, Walaa H.; Deghadi, Reem G.; Mohamed, Gehad G.
Abstract : A novel Schiff base ligand (H2 L) was prepared through condensation of 2, 6‐diaminopyridine and o ‐benzoylbenzoic acid in a 1:2 ratio. This Schiff base ligand was characterized using elemental and spectroscopic analyses. A new series of Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) metal complexes of H2 L were prepared and characterized using elemental analysis, spectroscopy ( 1 H NMR, mass, UV–visible, Fourier transform infrared, electron spin resonance ), magnetic susceptibility, molar conductivity, X‐raypowder diffraction and thermal analysis. The complexes are found to have trigonal bipyramidal geometry except Cr(III), Mn(II) and Fe(III) complexes which have octahedral geometry based on magnetic moment and solid reflectance measurements. The infrared spectral studies reveal that H2 L behaves as a neutral bidentate ligand and coordinates to the metal ions via the two azomethine nitrogens. 1 H NMR spectra confirm the non‐involvement of the carboxylic COOH proton in complex formation. The presence of water molecules in all reported complexes is supported by thermogravimetric studies. Kinetic and thermodynamic parameters were determined using Coats–Redfern and Horowitz–Metzger equations. The synthesized ligand and its complexes were screened for antimicrobial activities against two Gram‐positive bacteria ( Bacillus subtilis and Staphylococcus aureus ), two Gram‐negative bacteria ( Escherichia coli and Neisseria gonorrhoeae ) and one fungus ( Candida albicans ). Anticancer activities of the ligand and its metal complexes against human breast cancer cell line (MCF7) were investigated. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : IC50 of macrocyclic Schiff base ligand (H2 L) and its metal complexes.